Fabrication of Biocompatible Transdermal Nanofibrous Patch for Localized Delivery of Lidocaine and Rosemary Oil to Improve Effective Management of Lymphoma Pain and Nursing Care - Guo, Yanjing; Li, Ningning; Chen, Xingyu; Wang, Tao; Zhang, Wenping; Wu, Lihua (Indian Journal of Pharmaceutical Education and Research, 2024)
Background The primary goal of the current investigation is to fabricate a transdermal NFs patch-based drug delivery system using Poly-N-Vinyl Caprolactam (PNVCL) blended with sodium alginate to prepared transdermal nanofibrous patch for lymphoma pain and nursing care, with lidocaine and Rosemary oil, as supportive drugs for pain management. Materials and Methods The local anaesthetic Lidocaine (LP) and natural drug Rosemary Oil (RO) were loaded into the temperature transition phase of polymer at 35°C. The LP and RO encapsulated gel was grafted onto the electrospun fabricated nanofibrous R-LP@NFs (Lidocaine loaded rosemary oil fabricated nanofibers) patch for thermal responsive delivery. In vitro cumulative release of RO and LP was examined to investigate triggered delivery. Results The observed drug release profiles exhibited that higher release at pH 5.5 and 39°C. In order to measure the plasma concentration of lidocaine, patches were administered onto rat model at lymphoma site during the in vivo investigation. The acquired results demonstrated that the thermoresponsive R-LP@NFs patch have the potential to localised delivery system for pain management. Conclusion The developed transdermal nanofibrous patch offers a promising approach for the localized delivery of lidocaine and rosemary oil to improve the effective management of lymphoma pain and nursing care. The controlled release of drugs from the patch demonstrates its potential as a targeted drug delivery system, highlighting its suitability for clinical applications in lymphoma pain management.
Keywords: Transdermal patch; Lidocaine; Rosemary oil; Lymphoma pain; Nursing care